Sustainability empowerment in the workplace: determinants and effects - Christoph Harrach; Sonja Geiger; Ulf Schrader (Sustainability Management Forum, 2020)
There is a~dynamic stream of research, which examines why and how employees contribute and respond to corporate social responsibility (CSR). Building on these micro-CSR findings, this article makes a~contribution to a~better understanding of employee engagement in CSR by considering its determinants and effects. The research centres around the established motivational concept of psychological empowerment in the workplace and applies it to sustainability. The authors propose a~model of sustainability empowerment in the workplace (SEW) and empirically test the construct in a~comprehensive framework. Results indicate that the sustainability-orientation of employees and the perceived organisational support towards sustainability act as two valid determinants of SEW. It is also shown that SEW has positive effects on job satisfaction and organisational commitment. Further results indicate that the sustainability-orientation of employees plays an important role as a~moderator in the relationship between SEW and its effects. In the overall view, the paper contributes to micro-CSR research by showing that SEW is a~valid construct that helps to answer why and how employees engage in CSR activities and what positive effects arise therefrom for organisations. The authors give an overview of these contributions and discuss the implications for researchers and practitioners in the field of CSR and HRM.
Keywords: 650; Corporate social responsibility; Micro-CSR; Sustainability; Human resource management; Psychological empowerment